Analysis of the Relationship Between Emotional Intelligence, Organizational Culture, and Job Satisfaction on Employee Performance at Urban Village Offices in Palu Barat District - Rahmiwati Habibu; Farid; Cristian (IECON: International Economics and Business Conference, 2025)
This study aims to analyze the influence of emotional intelligence, organizational culture, and job satisfaction on employee performance at urban village offices in Palu Barat District. The research employed a survey method with a quantitative approach, where the entire population of 45 employees was taken as the sample using a total sampling technique. Data were collected through questionnaires, observations, interviews, and documentation, and then analyzed using multiple linear regression with SPSS 25. The findings reveal that emotional intelligence, organizational culture, and job satisfaction have a positive and significant effect on employee performance, both partially and simultaneously. The coefficient of determination of 75.9% indicates that employee performance can be explained by these three independent variables, while the remaining 24.1% is influenced by other factors outside the scope of this study. These results emphasize the importance of managing emotional intelligence, fostering a supportive organizational culture, and enhancing job satisfaction to improve employee performance, particularly in delivering public services at the village office level.